Kontestasi Komodifikasi Media Massa dan Ideologi Muhammadiyah - Mariana Ulfah (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This study aims to determine the contestation commodification and mass media Muhammadiyah ideology. Television media industry is a capital intensive industry types. This compares with the strength to build a perception in society, resulting in the attraction of various interests disana.Pada generally a television station is affected by the strength of the owner, the advertising, and rating. One local TV station, ADiTV, has the additional element that also affects the identity tayangannya Muhammadiyah, as its founder. In this study, using a qualitative descriptive. Through descriptive method will be able to explain the phenomenon in detail and presents a more detailed analysis that can not afford revealed by quantitative methods. The identity of a television media is very important to determine the standard of impressions and development of the company in the long term. Ambiguity status Muhammadiyah TV ADiTV whether or not can be detrimental for both parties ADiTV either alone or Muhammadiyah. ADiTV losses include the whole range ADiTV can not freely determine the policy, especially pertaining to the propaganda value of Muhammadiyah